PENGARUH KONSENTRASI LARUTAN MADU LEBAH HUTAN (Apis dorsata) TERHADAP HAMBATAN PERTUMBUHAN BAKTERI Porphyromonas gingivalis DOMINAN GINGIVITIS (Kajian in vitro) - Wachidah, Rizky Nurlailatul, drg. Mahmud Kholifa, MDSc, drg. Retno Sari (2016)
Gingivitis is an inflammation of the gingiva caused by acteria and result changes in shape, color and consistency without attachment loss. The main cause of gingivitis was the microorganisms found in dental plaque, one of which was Porphyromonas gingivalis. Gingivitis can be prevented by reducing plaque score effectively by mechanical means (brushing and flossing) or combined with chemical means (mouthwash). The used of natural materials can be an alternative material because chemicals feared causing toxicity. The forest honey bee solution that has been known which had antibacterial properties and widely consumed by public. This study aimed to determine the influence of forest honey bee (Apis dorsata) solution against the bacteria Porphyromonas gingivalis growth inhibition dominant gingivitis. This research was conducted with diffusion method was by measuring the diameter of the transparent zone around the wells petri dish. The suspension of the bacteria Porphyromonas gingivalis that has been rubbed on a petri dish by the addition of honey bees concentration of forest 15%, 30%, 60%, 90% and positive control (chlorhexidin). Fifth petri dishes were incubated at 37°C for 24 hours. Inhibition zone formed was measured using a vernier caliper with a precision of 0.02 mm. The average zone of inhibition on research using a solution of honey bees forests concentration of 15% was 9,75mm, a concentration of 30% was 11,12mm, a concentration of 60% was 13,03mm and a concentration of 90% was 16,07mm. Anova statistical test result obtained by the result of p = 0.00 (p <0.05). The results showed the addition of honey bees concentration woods significant effect on growth inhibition of bacteria Porphyromonas gingivalis dominant gingivitis. LSD Post Hoc test showed p = 0.00 (p <0.05), which means that any increased barriers to the growth of bacteria Porphyromonas gingivalis significantly. The conclusion from this study that forest honey bees (Apis dorsata) solution effect the growth inhibiting of bacteria Porphyromonas gingivalis dominant gingivitis in vitro at concentrations of 15%, 30%, 60% and 90%.